2006
DOI: 10.1152/japplphysiol.00268.2006
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen treatment after experimental hypoxia-ischemia in neonatal rats alters the expression of HIF-1α and its downstream target genes

Abstract: Recently, mounting evidence has emerged to suggest that hyperbaric oxygenation (HBOT)-induced neuroprotection after experimental global ischemia and subarachnoid hemorrhage entails a decrease in the expression of hypoxia-inducible factor-1alpha (HIF-1alpha). Therefore, the purpose of this study was to test the hypothesis that oxygen-induced neuroprotection after neonatal hypoxia-ischemia involves alterations in the expression of HIF-1alpha. Seven-day-old rat pups were subjected to unilateral carotid artery lig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
47
0
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(52 citation statements)
references
References 49 publications
3
47
0
2
Order By: Relevance
“…Our previous studies as well as others have shown that HIF-1α protein levels increased and peaked at 3-4 hr after hypoxic-ischemic injury (Calvert et al, 2006;van den Tweel et al, 2006), at 7.5 hrs after focal cerebral ischemia in adults and at 96 hrs in adult global ischemic model (Jin et al, 2000;Li et al, 2005). The ineffectiveness of 2ME2 when administered at 3 h after HI in the present study strongly suggested that neuroprotective effects are dependent on early HIF-1α inhibition i.e.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Our previous studies as well as others have shown that HIF-1α protein levels increased and peaked at 3-4 hr after hypoxic-ischemic injury (Calvert et al, 2006;van den Tweel et al, 2006), at 7.5 hrs after focal cerebral ischemia in adults and at 96 hrs in adult global ischemic model (Jin et al, 2000;Li et al, 2005). The ineffectiveness of 2ME2 when administered at 3 h after HI in the present study strongly suggested that neuroprotective effects are dependent on early HIF-1α inhibition i.e.…”
Section: Discussionsupporting
confidence: 75%
“…A modified Rice-Vannucci model (Rice et al, 1981) was adopted as follows (Calvert et al, 2006): 7-day-old postnatal pups were anesthetized with isoflurane (3% in a mixture of medical air and oxygen 70:30 ratio). The right common carotid artery of each pup was identified, exposed, and permanently ligated with 5-0 surgical silk through a near-midline incision.…”
Section: Animal Modelingmentioning
confidence: 99%
“…3,[9][10][11] In neurons, phosphorylated cyclic AMP-regulatory element-binding (pCREB) protein and the mouse Y box-binding protein-1 (MSY-1) bind the Glut3 12 Phosphorylation of CREB has been linked to neuroprotection both in vitro and in vivo ischemia models. 13,14 CREB is phosphorylated using multiple kinases including protein kinase A (PKA), calcium-calmodulin kinases (CaMK), protein kinase B (PKB), protein kinas C (PKC), and mitogen-activated protein kinase/extracellular signal regulated kinase (MAPK/ERK, MEK).…”
Section: Introductionmentioning
confidence: 99%
“…A reduction in spinal cord tissue cystic necrosis and damage in the surrounding white matter following HBO treatment was also observed by Yeo et al (1977). HBO reduced apoptosis following SCI (Calvert et al 2006, Peng et al 2008, Wang et al 2009). Higgins et al (1981) studied spinal cord electropotentials and showed that early HBO treatment contributed to the prevention of progressive degeneration in SCI.…”
Section: Discussionmentioning
confidence: 94%